Gonorrhoea in women in Scotland. Evidence of cohorts having a higher or lower incidence than expected. Issue 4 (August 1979) - Schofield, C B
Abstract : Incidences of genital gonorrhoea in women higher or lower than expected occurred in patients aged 15–19 years four years after similar findings in those aged 10–14 years. This pattern was followed five years later in those aged 20–24, 11 years later in those aged 25–34, and 20 years later in those aged 35–44 years. Thus, cohorts of women at greater or lesser risk of acquiring gonorrhoea appear to exist. Most cohorts with a high incidence could be identified when in the 10–14 age group. Especially high rates of infection are predicted in the 25–34 age group in the mid-1980s and in the 35–44 age group in the late 1980s. These findings will affect the timing of health education on sexually transmitted diseases in schools and will demand a high degree of awareness among general practitioners, gynaecologists, and those working in family planning and well-women clinics of the possibility of gonorrhoea occurring in women in these age groups.